Peran Pendidikan Jasmani Terhadap Kesejahteraan Anak Usia Dini - Annisa Nur Azizah; Risbon Sianturi; Taopik Rahman; Jenny Nur Azizah; Ratna Mustika Sari; Millatussa’adah Millatussa’adah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Study results and review of related literature prove the importance of physical education plays a crucial role in promoting child well-being. Physical education not only focuses on physical activity but also encompasses mental, social, emotional, and cognitive development in a holistic manner. Scientifically, regular physical activity has been proven to improve biological body functions while also influencing children's psychological conditions. From a physical perspective, physical education contributes to improving physical fitness, motor coordination, and preventing various health problems from an early age. From a psychological perspective, physical activity can help alleviate stress and anxiety and enhance mood through the release of endorphins. In the social dimension, physical education helps foster interpersonal skills such as cooperation, communication, and sportsmanship. In addition, physical activity also supports cognitive functions, such as improving concentration, memory, and academic achievement. Thus, physical education is an essential component in improving the welfare of early childhood in a comprehensive and holistic manner